(untitled) (Semiárida, 2024)
Selective rolling is a technique applied for the control of woody plants in semi-arid ecosystems in order to improve the condition of the pasture and reduce the risk of fires. There are studies on the effect of rolling on the soil and herbaceous and shrubby vegetation in La Pampa, but there are no scientific studies on the growth of tree vegetation in the face of successive applications of the practice. The objective of the study was to evaluate the regrowth capacity of Neltuma flexuosa (algarrobo) shoots in the Caldenal-Monte Occidental ecotone region, La Pampa. It was developed in the Campo Anexo INTA Chacharramendi in two sites with different frequencies of selective rolling, site 1 with a single intervention and site 2 with four interventions. Both sites were affected by a fire in 2016. The regrowth capacity was evaluated by measuring the length, diameter and number of regrowth measured in 39 carob trees per site. No significant differences were found between the variables of each treatment. These results could be due to the low intensity of the disturbance that failed to affect the levels of reserves, allowing the regeneration of the species. The information generated in this study provides greater knowledge about the effectiveness of the rolling practice as a woody control strategy in arid-semiarid environments.